2016
DOI: 10.1098/rsob.160003
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in dynamic m 6 A RNA modification

Abstract: The identification of m6A demethylases and high-throughput sequencing analysis of methylated transcriptome corroborated m6A RNA epigenetic modification as a dynamic regulation process, and reignited its investigation in the past few years. Many basic concepts of cytogenetics have been revolutionized by the growing understanding of the fundamental role of m6A in RNA splicing, degradation and translation. In this review, we summarize typical features of methylated transcriptome in mammals, and highlight the ‘wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
255
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(260 citation statements)
references
References 99 publications
(255 reference statements)
3
255
0
2
Order By: Relevance
“…Recent evidence has shown that, in addition to Mettl3, there were other enzymes, like Mettl14 (26), Wilms tumor 1-associated protein (Wtap) (27), and KIAA1429 (28), also involved in the RNA methylation process. On the other hand, two m 6 A erasers, fat mass and obesity-associated (Fto) (29) and alkB homolog 5 RNA demethylase (Alkbh5) (30), have been found to be involved in m 6 A modification in mammalian cells (31). These findings suggest that the regulation of RNA methylation in eukaryotic cells is finely regulated through these m 6 A modification-associated factors.…”
Section: Discussionmentioning
confidence: 83%
“…Recent evidence has shown that, in addition to Mettl3, there were other enzymes, like Mettl14 (26), Wilms tumor 1-associated protein (Wtap) (27), and KIAA1429 (28), also involved in the RNA methylation process. On the other hand, two m 6 A erasers, fat mass and obesity-associated (Fto) (29) and alkB homolog 5 RNA demethylase (Alkbh5) (30), have been found to be involved in m 6 A modification in mammalian cells (31). These findings suggest that the regulation of RNA methylation in eukaryotic cells is finely regulated through these m 6 A modification-associated factors.…”
Section: Discussionmentioning
confidence: 83%
“…N 6 -adenosine methylation (m 6 A) is the most abundant RNA modification found in ϳ25% of RNA species in mammalian cells (1,2). Despite its discovery decades ago (3)(4)(5)(6)(7), the biochemical pathways responsible for m 6 A and the biological functions of this process were not fully defined until very recently (8)(9)(10). Three methyltransferases, including methyltransferase-like 3 (METTL3), methyltransferase-like 14 (METTL14), and Wilms' tumor 1-associated protein (WTAP), act as m 6 A writers and catalyze RNA m 6 A at specific sites with the consensus sequence [(G/A)GAC, where the underlined adenosine is the methylation site] (11,12).…”
mentioning
confidence: 99%
“…Producing eukaryotic mRNA, especially in animal cells, requires many biochemical steps including 5ʹ capping, 3ʹ polyadenylation, obligatory and alternative splicing of many exons and base modifications, the latter of which which has been much discussed recently with respect to N6 adenosine methylation of residues that exist in mRNA (He 2010;Fu et al 2014;Wang and He 2014;Cao et al 2016;Ke et al 2017;Meyer and Jaffrey 2017;Roundtree et al 2017). To reflect more directly on the recent mRNA methylation studies and commentaries, a look back at earlier and recent techniques and conclusions is in order.…”
mentioning
confidence: 99%